Equilibrative Nucleoside Transporter 2: Properties and Physiological Roles. (4th December 2020) - Naes, Safaa M.; Ab-Rahim, Sharaniza; Mazlan, Musalmah; Abdul Rahman, Amirah
Abstract : Equilibrative nucleoside transporter 2 (ENT2) is a bidirectional transporter embedded in the biological membrane and is ubiquitously found in most tissue and cell types. ENT2 mediates the uptake of purine and pyrimidine nucleosides and nucleobase besides transporting a variety of nucleoside-derived drugs, mostly in anticancer therapy. Since high expression of ENT2 has been correlated with advanced stages of different types of cancers, consequently, this has gained significant interest in the role of ENT2 as a potential therapeutic target. Furthermore, ENT2 plays critical roles in signaling pathway and cell cycle progression. Therefore, elucidating the physiological roles of ENT2 and its properties may contribute to a better understanding of ENT2 roles beyond their transportation mechanism. This review is aimed at highlighting the main roles of ENT2 and at providing a brief update on the recent research.